Facile green synthesis of silver nanodendrite/cellulose acetate thin film electrodes for flexible supercapacitors. (1st May 2017) - Devarayan, Kesavan; Park, Jiyoung; Kim, Hak-Yong; Kim, Byoung-Suhk
Highlights: Facile preparation of silver nanodendrite electrodes via ' in situ hydrogenation'. Flexible electrode withstands 5000 bending cycle with low resistance of ∼1 ohm/sq. A maximum specific capacitance of 237 F/g at a current density of 0.3 A/g. High cyclic stability with capacitance retention of 84% after 1000 cycle. Abstract: In this study, we present a highly efficient and economical solution called as ' in situ hydrogenation' for preparation of highly conductive thin film electrode based on silver nanodendrites. The silver nanodendrite (AgND)/cellulose acetate (CA) thin film electrodes exhibited sheet resistance ranging from 0.32 ohm/sq to 122.1 ohm/sq which could be controlled by changing the concentration of both silver and polymer. In addition, these electrodes exhibited outstanding toughness during the bending test. Further, these thin film electrodes have great potential for scale-up with an average weight of 3 mg/cm 2 and can be also combined with active nanomaterials such as multiwalled carbon nanotubes (MWCNTs) to fabricate AgND/CA/MWCNTs thin film for high-performance flexible supercapacitor electrode. The AgND/CA/MWCNTs electrodes exhibited a maximum specific capacitance of 237 F/g at a current density of 0.3 A/g. After 1000 cycles, the AgND/MWCNT/CA exhibited a decrease of 16.0% of specific capacitance.